Automated solid-phase extraction method for the determination of piperaquine in whole blood by rapid liquid chromatography. - Lindegårdh, N; Ashton, M; Bergqvist, Y (2003)
A bioanalytic method for the determination of piperaquine in whole blood by solid-phase extraction and rapid liquid chromatography has been developed and validated. Whole blood was hemolyzed with deionized water, and an internal standard was added to the samples before they were loaded onto a PRS cation-exchange solid-phase extraction column. Piperaquine and internal standard were analyzed by liquid chromatography on a Chromolith Performance (100 x 4.6 mm) column with mobile phase acetonitrile:phosphate buffer, I = 0.1, pH 2.5 (8:92, vol/vol), flow rate 4 mL x min-1, and UV detection at 345 nm. The intraassay precision for whole blood was 3.2% at 3.00 microM and 12.3% at 0.100 microM. The interassay precision for whole blood was 1.8% at 3.00 microM and 5.2% at 0.100 microM. The lower limit of quantification and the limit of detection were 0.050 microM and 0.010 microM, respectively.